A Bibliometric Analysis and Visualization of the Top-Cited Publications in Mild Traumatic Brain Injury - Shi, Jian; Du, Xianping; Cavagnaro, María José; Li, Na (Frontiers in Neurology, 2021)
BACKGROUND: For measuring their impact in scientific research the citation count of the publications is used in the bibliometric analysis, though still in the bibliometric analysis there is no comprehensive summary of mild traumatic brain injury (mTBI) research. This article intends to provide the physicians and the neuroscientists with a reference guide to assess the most influential publications written on this subject through a macroscopic view of the research activities on mTBI. METHODS: The database of the Web of Science was used to compile the 100 top-ranking publications on mTBI. The selected publications were evaluated on the basis of the several categorizations including the type of the publications, the number of citations, the country of origin, and the year of publication. RESULTS: Between 1946 and 2020, the 13040 publications that were published were included in the database. The least cited publications received 274 citations, while the most cited received 1748. Altogether, 71 publications were from the USA while 29 were from other countries. Among all the institutions, the University of Pittsburgh Medical Center led the list with 6 publications. Around 100 papers mostly on the clinical studies in the categories of neurology and neurosciences were published in 54 different journals. CONCLUSIONS: This study provides both transverse section summary and historical retrospect for the clinical advances of mTBI, and the publications of important observations that contributed significant impact on the treatment and prevention of mTBI had been identified.